Prognostic value of immunological data, in vitro antibody production, and virus culture in vertical infection with HIV-1. Issue 6 (June 1995) - García Rodriguez, M C; Bates, I; de José, I; Hawkins, F; Martinez-Zapico, R; Ferreira, A; Fontán, G
Abstract : The prognostic value of immunological indices, in vitro antibody production, and virus culture pattern at 3 months of age was estimated in 35 infants infected by HIV-1 from a cohort of 298 babies born to HIV-1 seropositive mothers and followed up from birth. At 1 year old, 15 of these infants were classified as stage P-1 (according to the Centers for Disease Control classification) seven were P-2A, and seven had AIDS. Significantly higher CD8 percentages, lower percentages and absolute value of CD4, and lower CD4/CD8 ratios at 3 months were observed in infants with severe symptoms at 1 year of age when compared with those who were asymptomatic at this age. Seventy seven per cent of infants with a 'rapid' virus culture when 3 months old had developed AIDS or had died by 1 year of age and only 8% of those with 'slow' virus culture had AIDS when 1 year old. Moreover, 100% of those who were asymptomatic at 1 year had a slow virus culture at 3 months. Significant statistical association was found between the virus replication pattern at 3 months and the clinical stage at 1 year of age.